Probability for a Wiener process to reside in tube domains for a long period of time - Gasanenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We give various representations of asymptotics for the probability for a Wiener process to reside within a curvilinear strip during extended time intervals.